CONDUCTING JOB ANALYSIS OF â€œMUST EVANâ€™S COMPANYâ€ TO REDUCE UNBALANCE JOB BETWEEN THE WORKERS - Suhardi, Josephine Marcella; Putranto, Nur Arief Rahmatyah (Journal of Business and Management, 2017)
Abstract. Apparel industry is a potential industry in Indonesia because it can be seen by its stagnant growth revenue towards improvement of gross domestic product Indonesia on the last 5 years. As one of the apparel company which contribute to those growth, Must Evan’s must have a good management team in order to maintain the sustainability of company’s performance. But from the interview result toward an employee in Must Evan’s, Preliminary research done at head quarter of Must Evan’s showed that it seems like there is an unbalance job responsibility between one employee and the other employee. Moreover, preliminary research done to several employees in Must Evan’s showed that majority of the employees are not satisfy with the division of work in Must Evan’s. Most of them said that it happened because they often doing work that is not accordance with the division. Therefore, this research aims to improve satisfaction of employee at Must Evan’s by help them understand the duties that need to be done. This can be done by conducting job analysis for this company, since there is no job list at all could become their guideline in doing a duties. This research using some interview result and some secondary data such as organization structure in order to conduct job description and job specification clearly. Researcher using Spencer and Spencer dictionary as a tool for determine the competencies needed by company to be a part of its job specification. The result of job analysis was compared to the current job that is done in Must Evan’s and it turns out that there are some positions that having overlap duties and some job division gave unfair job toward one workers and the other workers. However, with the new job analysis, it could reduce employee’s ignorance about the duties to be done. With this result of job analysis research, the result is may not be able to be used by other similar apparel company. However, the method still could be used in order to design a clear job list for employees. Keywords: Job Analysis; Human Resource Management